(untitled) (Eurasian Medical Research Periodical, 2026)
This article presents a detailed retrospective analysis of comorbidity in patients with age-related cataract. The study covers clinical data from 30 patients, including ophthalmological status, presence of diabetes mellitus, and cognitive function indices. Using variation statistics methods (Student’s t-test), the significant influence of hyperglycemia on accelerating the rate of lens degradation was demonstrated. A correlation between visual impairment and reduced cognitive reserve according to MMSE and MoCA scales was identified.